(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper holistically reviewed the present emergency response operations of the Lagos State Emergency Management Authority (LASEMA), and identified deficiencies. This ultimately led to the development of an improved network, premised on the assumption that all the response management sub-stations (LRU) of LASEMA in Lagos State were networked to a central location where all command operations are easily disseminated. An improved framework was then designed, that utilised an improved Ant Colony Optimization technique layered on the Google Map functionality to determine the shortest route to an incident site for the emergency vehicle conveying the first responders to the incident site. A detailed discussion on the design, development, implementation and evaluation approaches used for the Emergency Response Management System (ERMS) was done. How data used in this work were collected, tested for quality of its contents and then analysed using the descriptive analysis of the Statistical Package for Social Sciences (SPSS) software was extensively discussed. Also, the data collected before and after the implementation of the developed Emergency Response Management System (ERMS) were analysed using the descriptive analysis of the SPSS software, as to measure the perceived performance of the system, based on the variables defined from the Technology Acceptance Model (TAM). From the analyses of the results of these metrics, we concluded that the ERMS was able